Los contenidos básicos de la educación para la Paz (Journal of Parents and Teachers, 2014)
Achieving world peace and the fulfillment of fundamental rights is one of the social and, therefore, educational challenges. Thus, the article navigates through the contents related to peace education, consideringthe evolution of the concept and the importance of building social structures. In this way, concepts such as the positive valuation of conflicts and the elimination of violence as a tool for their resolution acquire special importance. Likewise, the desire to dominate and competitivenessare presented as obstacles to achieving peace. Finally, the importance of creating democratic schools that are based on the values of peace that they want to promote, where interpersonal relationships are essential.
Keywords: peace, education, contents, democracy